VALIDITY AND RELIABILITY OF SUMMATED XEROSTOMIA INVENTORY INDONESIAN VERSION IN SJOGREN’S DISEASE PATIENTS - Felicia Paramita; Endah Ayu Tri Wulandari (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Dry mouth is one of the hallmark symptoms in Sjogren’s disease. Dry mouth can be described as xerostomia and hyposalivation. Hyposalivation is objectively measured while xerostomia is subjective complaint which only can be measured using questionnaire. Purpose: To check the validity and reliability of Summated Xerostomia Inventory Indonesian Version (SXI-ID) in Sjogren’s disease patients. Methods: This is a cross-sectional study including Sjogren’s disease patients in Yayasan Sjogren’s Disease Indonesia. Data were collected using Google Form and analyzed using SPSS. Results: The result of validity test using Cronbach alpha was 0.83 and reliability test using interclass correlation coefficient was 0.98. Conclusion: Summated Xerostomia Inventory Indonesian Version (SXI-ID) is valid and reliable to be used among Sjogren’s disease patients. Keywords: hyposalivation, indonesia, sjogren’s disease, summated xerostomia inventory, validity and reliability, xerostomia